Kiss me Kate [videorecording (DVD)] - Sidney, George, 1916-2002; Grayson, Kathryn, 1922-2010; Keel, Howard, 1919-2004; Miller, Ann, 1923-2004; Wynn, Keenan, 1916-1986; Porter, Cole, 1891-1964 (Classic musicals collection., 2003)
Two squabbling, 20th-century ex-marrieds are cast as squabbling Renaissance romantics in a musical version of The taming of the shrew. On stage they fight it out and backstage they continue to clash.